Effects of 2,4-Di-tert-butylphenol and selected herbicides which induced lipid peroxidation on quantum yield and membrane integrity of weedy plants under dark and light conditions - Naimah Abdul Halim; Ma, Nyuk Ling; Ismail Sahid; Chuah, Tse Seng (Penerbit Universiti Kebangsaan Malaysia, 2018)
2,4-Di-tert-butylphenol (2,4-DTBP) has herbicidal properties that cause lipid peroxidation on plant tissues. The present study aimed at examining the phytotoxic effects of 2,4-DTBP compared to that of selected herbicides which induced lipid peroxidation based on quantum yield (Φ) and membrane integrity of two bioassay weed species namely Oldenlandia verticillata and Leptochloa chinensis under light and dark conditions. Laboratory assays showed reduced Φ of 2,4-DTBP- and dinoterb-treated leaf discs within the first 3 h of the dark incubation period, with further decrease during the subsequent 15 h dark period and 6 h light period. Diuron drastically reduced the Φ of the bioassay species throughout the incubation period. The Φ of glufosinate-treated O. verticillata leaf discs was marginally reduced and decreased further upon light exposure; it had no effect on the Φ of L. chinensis. Fluridone, isoxaflutole, clomazone and oxyfluorfen also had negligible effect on Φ, whereas paraquat caused a rapid reduction in Φ upon light exposure for both bioassay species. 2,4-DTBP, paraquat and dinoterb induced electrolyte leakage during the dark incubation period; this was further increased in the presence of light for O. verticillata and L. chinensis. For both bioassay species, glufosinate caused a marked amount of electrolyte leakage, whereas diuron, fluridone, isoxaflutole, clomazone and oxyfluorfen had negligible effect on ion leakage. These results suggested that 2,4-DTBP has herbicidal activity comparable to that of dinoterb without dependence on light.